2009
DOI: 10.1063/1.3176434
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport properties of p-type carbon-doped ZnO thin films

Abstract: Carbon-doped ZnO ͑ZnO:C͒ thin films exhibiting Curie temperature above room temperature were fabricated using ion beam technique. The magnetic moment of the ZnO:C films was found to be around 1.35 B per carbon atom. The ZnO:C films showed p-type conduction with a hole concentration of ϳ5 ϫ 10 17 cm −3 . In addition, the anomalous Hall effect and negative magnetoresistance can be detected in the ZnO:C films. The magnetotransport properties of the ZnO:C suggested that the films possessed charge carrier spin pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 12 publications
(10 reference statements)
3
49
0
Order By: Relevance
“…4͒ and carbon-doped ZnO ͑ZnO:C͒. 5,6 Among these d 0 oxides, ZnO:C has received significant attention because of its potential application in spintronics. Peng et al 7 showed that direct hole doping at the anion site, such as C substitution on the O site, was more effective for localizing the hole and sustaining the magnetic moment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4͒ and carbon-doped ZnO ͑ZnO:C͒. 5,6 Among these d 0 oxides, ZnO:C has received significant attention because of its potential application in spintronics. Peng et al 7 showed that direct hole doping at the anion site, such as C substitution on the O site, was more effective for localizing the hole and sustaining the magnetic moment.…”
mentioning
confidence: 99%
“…Indeed, p-type conduction and anomalous Hall effect have been observed experimentally in ZnO:C thin films. 6 Peng et al 7 also predicted that quantum confinement effect could reduce the critical hole concentration to induce ferromagnetism in ZnO nanostructures. However, it has been proved challenging to incorporate C into ZnO nanostructures effectively by conventional methods.…”
mentioning
confidence: 99%
“…Reported observations of ferromagnetism in the transition metal (TM) doped TiO 2 , SnO 2 , ZnO, are the most notable among them [2][3][4]. However, the role played by transition metals in manifestation of ferromagnetism in these systems has been seen with reservation after observation of ferromagnetism in ZnO with carbon-doping and even without any doping [5][6][7]. The query becomes more robust when ferromagnetism is surprisingly seen in thin films of band insulator HfO 2 even in the absence of any doping [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kwak et al predicted that the carbon dopants can become magnetic under confinement in ZnO nanocrystals and nanowires [7]. Herng et al obtained p-type magnetic ZnO using ion implantation [8]. Due to the polymorphism of carbon in these semiconductors, the modulation mechanisms of these properties, including carriers, local moment, and transport behaviors under magnetic field, vary significantly.…”
Section: Introductionmentioning
confidence: 99%